2000
DOI: 10.1029/1999gl011267
|View full text |Cite
|
Sign up to set email alerts
|

Halogen ions and NO+ in the mass spectra of aerosols in the upper troposphere and lower stratosphere

Abstract: Abstract. Mass spectra of individual aerosol particles were acquired at altitudes up to 19 km during the WB-57 Aerosol Mission. Fluorine and chlorine were more abundant in tropospheric aerosols than in stratospheric aerosols. Chlorine in tropospheric aerosols was often associated with organics, soot, and mineral dust. Small amounts of perchlorate were observed in stratospheric sulfate aerosols, but aerosols do not represent a significant sink for total fluorine or chlorine in the lower stratosphere. Bromine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 20 publications
(6 reference statements)
3
51
0
Order By: Relevance
“…Ko et al (1997) suggested a direct PG injection into the stratosphere, which could be due to bromine tied in aerosols (Murphy and Thompson, 2000) or in gaseous form (e.g., HBr, Br, BrO...). Comparing Br in y to tropospheric trend measurements of CH 3 Br and the halons taken from Montzka et al (2003), where no tropospheric loss of CH 3 Br is assumed, yields a VSLS plus PG injection of 5.2 ppt into the stratosphere (see also Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ko et al (1997) suggested a direct PG injection into the stratosphere, which could be due to bromine tied in aerosols (Murphy and Thompson, 2000) or in gaseous form (e.g., HBr, Br, BrO...). Comparing Br in y to tropospheric trend measurements of CH 3 Br and the halons taken from Montzka et al (2003), where no tropospheric loss of CH 3 Br is assumed, yields a VSLS plus PG injection of 5.2 ppt into the stratosphere (see also Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, investigation of only the SG injection may fall short in properly budgeting Br y , since it ignores the contribution of Br tied to aerosols, and inorganic bromine species (e.g., HBr, BrO). Evidence for a sizeable inorganic product gas (PG) contribution has been found in recent field and theoretical studies and consequences for stratospheric ozone have been discussed (e.g., Pfeilsticker et al, 2000;Murphy and Thompson, 2000;Salawitch et al, 2005;Salawitch, 2006;Law and Sturges, 2007). performed direct sun measurements during balloon ascent, from 2 to 33 km altitude, and during sunset at balloon float altitude (33 km) in solar occultation.…”
Section: Introductionmentioning
confidence: 99%
“…A direct product gas injection as proposed by Ko et al (1997) could also cause the difference in Br y by bringing inorganic bromine species contained in the upper tropospheric aerosol (Murphy and Thompson, 2000) or in gaseous form into the stratosphere. Another option is the presence of additional brominated organic substances.…”
Section: Inorganic Chlorine and Brominementioning
confidence: 99%
“…Law and Sturges (2007) used available data at altitudes between 10 and 17.5 km from six measurement campaigns that were carried out within a period of eight years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) to assess the amount of chlorine and bromine from VSLS that is present in the tropical upper troposphere. Also several model studies were performed to quantify in particular the influence of brominated VSLS to ozone depletion (Dvortsov et al, 1999;Nielsen et al, 2001;Levine et al, 2007). Current estimates of the World Meteorological Organisation for the upper tropical troposphere range from 52 to 60 ppt for chlorine and 3.1 to 4.0 ppt for bromine from VSLS, but measurements show a much higher variability and uncertainty (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Deep convective events could also transport iodine-containing particles into the dry upper troposphere where the particles can survive wash-out, climb into the stratosphere and eventually evaporate at higher altitudes. Murphy et al (1998), Murphy and Thomson (2000), and Murphy et al (2007) indeed found iodine in upper tropospheric and lower stratospheric particles. Most studies investigating the abundances of inorganic iodine species (IO and/or OIO) in the stratosphere conclude undetectably low amounts (Wennberg et al, 1997;Pundt et al, 1998;Bösch et al, 2003;Berthet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%